2015
DOI: 10.15171/joddd.2015.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Non-surgical Periodontal Therapy on Serum and Salivary Concentrations of Visfatin in Patients with Chronic Periodontitis

Abstract: Background and aims. Visfatin, mainly secreted by visceral adipose tissue, especially by macrophages, plays an important role in regulating the defense and immune functions, and functions as a growth factor, a cytokine, an enzyme and more importantly as a proinflammatory mediator. The aim of the present study was to evaluate the effect of non-surgical periodontal treatment on serum and salivary levels of visfatin in patients with generalized moderate-to-severe chronic periodontitis.Materials and methods. Eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
4
13
0
1
Order By: Relevance
“…Then, Raghavendra et al 36 showed that increased GCF visfatin levels in periodontitis reached levels similar to those in healthy individuals after periodontal treatment. In additional studies, this adipokine in saliva was found to be a marker of inflammation in periodontal disease, and the levels in saliva decreased after periodontal treatment 25 , 37 . In this study, the level of visfatin in GCF in patients with periodontitis was higher compared with that of the healthy individuals, which is consistent with these other studies.…”
Section: Discussionsupporting
confidence: 90%
“…Then, Raghavendra et al 36 showed that increased GCF visfatin levels in periodontitis reached levels similar to those in healthy individuals after periodontal treatment. In additional studies, this adipokine in saliva was found to be a marker of inflammation in periodontal disease, and the levels in saliva decreased after periodontal treatment 25 , 37 . In this study, the level of visfatin in GCF in patients with periodontitis was higher compared with that of the healthy individuals, which is consistent with these other studies.…”
Section: Discussionsupporting
confidence: 90%
“…They reported that non-surgical periodontal treatment reduced visfatin and HbA1c levels in periodontitis patients with T2DM. The serum and salivary levels of visfatin were also shown to decrease significantly after non-surgical periodontal treatment (39). In the present study, a significant decrease in visfatin levels was observed 1 month after non-surgical periodontal treatment in gingivitis and CP individuals.…”
Section: Discussionsupporting
confidence: 69%
“…In several studies, high levels of visfatin have been reported in saliva, GCF, and periodontal tissue in periodontitis 6,7,41‐43 . In contrast, visfatin GCF and saliva levels have been reported to decrease after NSPT 15–18 . In another study by the present authors’ research group, it was suggested that the microbiologic agents that colonize the subgingival region in periodontitis can increase visfatin expression 19 .…”
Section: Discussionmentioning
confidence: 61%
“…Its role in periodontal inflammation has been demonstrated in several recent studies. Increased levels in saliva and gingival crevicular fluid (GCF) were found to decrease after non‐surgical periodontal therapy (NSPT) 15–19 . Chemerin is another proinflammatory adipokine with a different mechanism 20 .…”
mentioning
confidence: 99%